2006
DOI: 10.1111/j.1525-1438.2006.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite instability in endometrioid endometrial carcinoma: correlation with clinically relevant pathologic variables

Abstract: This study of 218 patients with endometrioid endometrial carcinoma explores the relationship between microsatellite instability (MSI) as established by the BAT26 method and the common pathologic variables of prognostic and therapeutic significance. MSI was positively correlated with grade, associated endometrial atrophy, squamous metaplasia, isthmic involvement, depth of myoinvasion, vascular invasion-associated changes, extrauterine tumor spread, and extramyometrial angiolymphatic spread. There was no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 58 publications
1
24
1
Order By: Relevance
“…MSI-L and MSI-H were found in 11% and 16% of the cancers analyzed (totalling 27%). Of 17 previous studies on MSI in endometrial cancer, the prevalence of MSI widely varied from 9% to 45% [1,4,5,7,10,12,16,17,19,25,26,28,29,32,33,42,44] (Table 1). The table also illustrates the enormous variation in the numbers of patients, stages, histotypes and molecular techniques used in the different studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MSI-L and MSI-H were found in 11% and 16% of the cancers analyzed (totalling 27%). Of 17 previous studies on MSI in endometrial cancer, the prevalence of MSI widely varied from 9% to 45% [1,4,5,7,10,12,16,17,19,25,26,28,29,32,33,42,44] (Table 1). The table also illustrates the enormous variation in the numbers of patients, stages, histotypes and molecular techniques used in the different studies.…”
Section: Discussionmentioning
confidence: 99%
“…Increased understanding of the molecular biology in endometrial carcinogenesis has revealed several promising prognostic and predictive biomarkers, such as microsatellite instability (MSI), a characteristic finding in cancers deficient in DNA mis-match repair (MMR), seen in 9-45% of sporadic endometrial cancers (Table 1) [1,[4][5][6][7]10,12,16,17,19,25,26,28,29,32,33,42,44]. In contrast to Hereditary NonPolyposis Colorectal Cancer (HNPCC) or Lynch syndrome, which is an autosomal dominant condition involving germline MMR gene mutation, sporadic en- [15].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies from 2006 in a relatively large-scale cohort of EMC patients showed significant associations between tumor MSI-H and advanced tumor stage, myometrial invasion, and improved survival. 24,25 However, a later study, in 2014, showed no associations of MSI status with survival, tumor grade, tumor stage, or histologic examination findings in 109 patients. 26 In our study, a correlation between International Federation of Gynecology and Obstetrics grade and MSI status was observed.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of endometrial carcinoma, however, there have been only limited pathologic studies [5,[11][12][13]. Although certain pathologic parameters, such as histologic type, grade, extent of myometrial invasion, and lymphovascular invasion, have been suggested as related to the MSI phenotype, the data are relatively scant and the significance of such parameters in detecting MSI tumors remains to be defined.…”
Section: Introductionmentioning
confidence: 96%